2020
DOI: 10.1177/1533033820945802
|View full text |Cite
|
Sign up to set email alerts
|

SNHG7 Facilitates Glioblastoma Progression by Functioning as a Molecular Sponge for MicroRNA-449b-5p and Thereby Increasing MYCN Expression

Abstract: Background and Aims: Long noncoding RNA (small nucleolar RNA host gene 7) has been reported to be involved in multiple malignancies and acts as an oncogene. However, the potential mechanism of small nucleolar RNA host gene 7 in glioblastoma is rarely known. In this study, we attempted to elucidate the biological effects of small nucleolar RNA host gene 7 and the possible molecular mechanism in glioblastoma. Methods: The expression level of small nucleolar RNA host gene 7 in glioblastoma tissues and correspondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Chen et al found that the expression of SNHG7 was signi cantly increased in glioblastoma and could be used as a molecular sponge to negatively regulate the expression of miR-449b-5p. At this time, the expression of MYCN protein increased and reversed the antitumour effect of miR-449b-5p, thus promoting the proliferation, migration, and invasion of glioblastoma [44]. In another study, Wang et al found that SNHG7 was upregulated in non-small-cell lung cancer (NSCLC) and played an oncogenic role in their experiment.…”
Section: Discussionmentioning
confidence: 96%
“…Chen et al found that the expression of SNHG7 was signi cantly increased in glioblastoma and could be used as a molecular sponge to negatively regulate the expression of miR-449b-5p. At this time, the expression of MYCN protein increased and reversed the antitumour effect of miR-449b-5p, thus promoting the proliferation, migration, and invasion of glioblastoma [44]. In another study, Wang et al found that SNHG7 was upregulated in non-small-cell lung cancer (NSCLC) and played an oncogenic role in their experiment.…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, inhibition of miR-5095 in A172 and U-87 MG cells increased the expression of CTNNB1, the gene encoding β-catenin ( 72 ). More recently, Chen et al reported that SNHG7 acts as a miRNA sponge by reducing miRNA-449b-5p levels, increasing MYCN (a miRNA-449b-5p target gene), and promoting GBM progression ( 73 ). In other studies, Han et al reported that the Wnt/β-catenin signaling pathway in GBM is inhibited by the lncRNA MIR22HG through the loss of miR-22-3p and miR-22-5p ( 74 ).…”
Section: Deregulation Of Non-coding Rnas In Gbmmentioning
confidence: 99%
“…Small nucleolar RNA host gene 7 (SNHG7) is a newly identified lncRNA, which located on chromosome 9q34.3 and has a full length of 984 bp. It has been confirmed to be an oncogene in multiple tumors including glioblastoma, lung cancer, breast cancer, and hepatocellular carcinoma (9)(10)(11)(12). In non-small cell lung cancer, SNHG7 can inhibit microRNA (miRNA/miR)-181a-5p via the Akt/mTOR signaling, and facilitate cell proliferation, migration, and invasion (9).…”
Section: Original Articlementioning
confidence: 99%